THE POTENTIAL OF THE ISOLATED PROBIOTICS BACTERIAL FROM GIANT PRAWNS’ DIGESTIVE TRACT (Macrobrachium Rosenbergii, De Man) WITH 16S DNA SEQUENCES TECHNIQUE - Feliatra, Feliatra; Yoswaty, Dessy; Lukystyowati, Isye; Hasyimi, Wahid (Indonesian Aquaculture Society (MAI), 2014)
Probiotics is a bacterial product that has beneficial for fish; both for growth and body's defenses from bacteria desease. The aim of the study is to determine the types of candidate of probiotic bacteria from the digestive tract of giant prawns that is found in Teratak Buluh Pekanbaru, Riau. This research was conducted at the Laboratory of Microbiology and Biotechnology of Fishery Faculty of Fisheries and Marine Sciences University of Riau, Pekanbaru to get a candidate of Probiotic Bacteria and do molecular examination that consists of purification of electrophoresis gel and DNA sequencing at the Institute for Biotechnology Serpong, Tangerang Banten. The method of this study is a survey method that used physical and biochemical test and molecular identification . The results showed that eleven isolates of bacterial are the species Bacillus BDU4 strain from A Bacteria isolates with 99 % homology and 10 isolates of bacterial are bacillus genus because the degree of homology below 97% and they are considered as the original indonesia’s new species probiotic bacteria.